Djerba, Ethiopie : La piste africaine - Roten, Hervé (Yuval, 1993)
Keywords: Judaïsme -- Djerba

Djerba synagogue El-Ghriba - Tmarzizet, Kamel; Pérez, Jacques (Carthacom, 1993)
Keywords: Judaïsme -- Djerba

A Midrash about the Patriarch Abraham in the Passover Haggadah of Djerba / מדרש על אברהם אבינו בהגדה של פסח של יהודי ג'רבה - אילן, נחם; Ilan, Nahem (Sefunot: Studies and Sources on the History of the Jewish Communities in the East, 1993)
The Passover Haggadah is a unique ritual text because it is used in a religious ceremony celebrated at home with the participation of the entire family. The children are at the center of the event. Since the text is primarily Hebrew, whoever led the seder in various Jewish communities felt compelled to translate the text to the language spoken by Jews in that community so that the content of the Haggadah would be clear to all the participants and their children enabling them to fulfill the commandment 'And you will tell your son.' For this reason we find Haggadot in many Jewish languages. The Haggadah of the Jews of Djerba includes a passage in Arabic, which, according to the author of this article, does not appear in any other version. This Haggadah adds, after the passage: 'At first our fathers were idolators' an adaptation of three midrashic traditions on the Patriarch Abraham and how he came to acknowledge and believe in the one God even though he lived in a totally idolatrous environment. The article surveys the various Djerban traditions in which the passage appears, councluding that this text came to be included in the Djerban custom no later than the early eighteenth century. The text is presented revealing the variations in the way it was written, though changes of content were few and insignificant. Obviously the text is written in a very vulgar form of Judeo-Arabic as befits its function and purpose. A literary analysis of the text reveals how the midrashim were adapted to the seder service. Details that were irrelevant to the educational purpose of the seder were omitted and others were altered in order to fit better into the story of the Exodus from Egypt. In conclusion, the text is a witness to the dynamic character of the seder among the Jews of Djerba and a unique expression of the Passover Haggadah tradition in Djerba. In addition to its special context it may be added to the midrashic traditions concerning the Patriarch Abraham adding a unique Djerban dimension to them.
Keywords: Judaïsme -- Djerba